Invasive Spartina alterniflora changes the Yangtze Estuary salt marsh from CH4 sink to source. (5th May 2021) - Yang, Bin; Li, Xiuzhen; Lin, Shiwei; Jiang, Can; Xue, Liming; Wang, Jiangjing; Liu, Xiaotong; Espenberg, Mikk; Pärn, Jaan; Mander, Ülo
Abstract: Expansion of Spartina alterniflora salt marshes in the East China Sea coast is changing the ecosystem and thus, uncertainty has hampered methane (CH4 ) flux accounts in these areas. To analyse seasonal and diurnal patterns of the CH4 fluxes and their relationship with environmental factors, four plots were established in a salt marsh of the Nanhui coast in the southern fringe of the Yangtze River estuary, differing in sediment salinity and vegetation history and including one bare mudflat. Monthly studies from March 2017 to January 2018 using a chamber technique showed that CH4 fluxes from the plots ranged from −1.7 to 72.2 mg m −2 h −1 . The mature Spartina sites showed higher CH4 emission, peaking in the summer. In the mudflat CH4 consumption was observed in January and the summer. The seasonal CH4 fluxes showed positive correlation ( p < 0.05) with temperature, and plant development (height of vegetation), and negative correlation ( p < 0.05) with water salinity. Various diurnal cycles in the CH4 fluxes were observed at different seasons. Average CH4 emissions were higher during the daytime than at night, however, without significant difference. Thus, the CH4 fluxes started to rise at noon, and the maximum CH4 flux was observed after the ebb tide (at 18:00) during nighttime. The diurnal variation in CH4 fluxes showed a significant correlation with season but not with temperature. Graphical abstract: Image 1 Highlights: The Spartina alterniflora salt marsh was a CH4 source and the mudflat was a CH4 sink. Seasonal CH4 flux showed positive correlation ( p < 0.05) with temperature. Type and age of plant community was a major factor of the CH4 flux. Salinity affected spatial and temporal variability of CH4 flux.